(untitled) (Contemporary Journal of Social Science Review, 2024)
Madrassas have consistently and continuously played a vital role in consolidation and shaping the religious theories amongst Muslims. This study attempts to assess the contribution of selected socio-cultural factors on mothers’ preference about Madrassa education for their daughters in Faisalabad, Pakistan by using the binary logistic regression of the primary data. For this study, the married women from the rural areas of Faisalabad were selected and the total sample size was 200. Binary Logistic Regression Model was used for the analytical purpose and odds ratio was calculated. It was observed that the mothers’ preference about Madrasas education increased to a specific level as the age increased. Whereas, the mothers’ preference about Madrassa education was decreased with an increase in the education level. Family type and monthly income remained important factor in the study. The variable ‘Relative in Madrassa’ also has an important impact on mothers’ preference of Madrassa education for their daughters. Parents’ preference of Madrassa education over formal education for their daughters does not necessarily imply that they are financially weak.